2012
DOI: 10.5402/2012/763783
|View full text |Cite
|
Sign up to set email alerts
|

Screening for Celiac Disease in Children with Dental Enamel Defects

Abstract: Background. Dental enamel defects (DEDs) are seen in celiac disease (CD). Aim was to detect frequency of CD among such patients. Methods. This study included 140 children with DED. They were tested for CD. Gluten-free diet (GFD) was instituted for CD patients. A cohort of 720, age and sex-matched, normal children represented a control group. Both groups were evaluated clinically. Serum calcium, phosphorus, alkaline phosphatase, serum IgA, and tissue transglutaminase (tTG) IgG and IgA types were measured. Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 33 publications
0
18
0
2
Order By: Relevance
“…The first one, conducted in an Italian population, found positive serology for CD in 10 of the 52 children who had DEDs, resulting in 19.23% of positive diagnosis 14 ; the other study in an Egyptian population found similar results (17.86%). 18 Both studies showed a high prevalence, considering that the estimated worldwide prevalence of CD is approximately 1%. The lack of association found in the present study could be attributed, in part, to the small sample size or to the lower prevalence of CD in the Brazilian population.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The first one, conducted in an Italian population, found positive serology for CD in 10 of the 52 children who had DEDs, resulting in 19.23% of positive diagnosis 14 ; the other study in an Egyptian population found similar results (17.86%). 18 Both studies showed a high prevalence, considering that the estimated worldwide prevalence of CD is approximately 1%. The lack of association found in the present study could be attributed, in part, to the small sample size or to the lower prevalence of CD in the Brazilian population.…”
Section: Discussionmentioning
confidence: 98%
“…Martelossi et al revealed a 19.23% prevalence of CD in a group of Italians who presented with DEDs, 16 and in another study, CD was diagnosed in 17.86% of a sample of Egyptians patients with DEDs. 18 More studies are needed to confirm the hypothesis that children with DEDs could have undiagnosed CD. In addition, the chemical composition of dental enamel in CD has not yet been evaluated.…”
mentioning
confidence: 95%
“…It is thought that nutritional deficiency (especially hypocalcemia) caused by malabsorption may disturb the process of amelogenesis [26]. Reports on lower serum calcium concentration may be found in the literature [27].…”
mentioning
confidence: 99%
“…An Egyptian study with 140 children with DED and a control group of 720 children with no DED underwent serological screening for CD; both groups had no other features of CD. CD was diagnosed in 17.86% with DED in comparison to 0.97% in the control group 18 . An Italian study with 603 children with CD, systemic DED was detected in 32.4% (195/603) in comparison to 0.59% in healthy controls (52/6949) 15 .…”
Section: Clinical Presentationmentioning
confidence: 85%
“…in first degree relatives or in children from high risk groups (table 2) and a suspicion of CD should be raised and highlighted to the GMP for serological screening 12 . Furthermore, patients detected with DED at diagnosis of CD will require regular monitoring by dentists and adherence to GFD is likely to improve the symptoms 18 . Dentists also need to be aware of the different compounds that they use when carrying out various dental procedures, such as equipment's, dental fillings or retainers to ensure that they do not contain gluten.…”
Section: Managementmentioning
confidence: 99%